2005
DOI: 10.1007/bf03345374
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of autonomic activity in patients with subclinical hypothyroidism

Abstract: It has been shown that impaired cardiac autonomic activity is closely related with lethal arhythmias. Heart rate variability (HRV), analysis of beat-to-beat variations, is an important and widely used non-invasive method to assess autonomic function. Impaired cardiac autonomic activity and altered sympathovagal balance were previously documented in patients with hypothyroidism. However, the effect of subclinical hypothyroidism (SH) on autonomic function has not been studied yet. We aimed to investigate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 28 publications
2
24
0
5
Order By: Relevance
“…In the study of Sahin et al (15), no differences in LF and HF were found, whereas decreased SDNN was reported in the subgroup with TSH levels equal to or higher than 10 mIU/mL (N=13; 41.9% of total subclinical hypothyroidism group). In our sample, most cases of SCHypo were mild cases, with only 25 (0.27%) subjects presenting TSH levels higher than 10 mIU/L.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the study of Sahin et al (15), no differences in LF and HF were found, whereas decreased SDNN was reported in the subgroup with TSH levels equal to or higher than 10 mIU/mL (N=13; 41.9% of total subclinical hypothyroidism group). In our sample, most cases of SCHypo were mild cases, with only 25 (0.27%) subjects presenting TSH levels higher than 10 mIU/L.…”
Section: Discussionmentioning
confidence: 87%
“…Although some heterogeneity exists, most studies on subclinical thyroid disorders reported an autonomic imbalance with lower HRV indices in both subclinical hyperthyroidism (SCHyper) (1012) and hypothyroidism (SCHypo) (1315). Evaluating the relationship between the subclinical dysfunctions and HRV may depict an important scenario regarding the underlying cardiovascular risk in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular system is very sensitive to minimal defects of circulating thyroid hormones, and cardiovascular disorders are usually associated with overt hypothyroidism (6)(7)(8). Furthermore, the abnormalities in myocardial contractility and the changes of the lipoprotein profile that are frequently documented in hypothyroid patients have been reported (6,8,9). Therefore, sHT may be considered a true risk factor for the development of coronary heart disease (6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…(12) Este aumento está associado com os níveis das catecolaminas plasmáticas e índice de dispersão do segmento QT. (11,25,(54)(55) Akcakoyun et al (10) investigaram a influên-cia do hipotireoidismo subclínico na resposta ao exercício físico em termos de recuperação da frequência cardíaca e competência cronotrópica.…”
Section: Potenciais Contribuições Do Exercício Físico Nas Disfunções unclassified
“…(1,(4)(5) As disfunções cardiovasculares já são observadas no hipotireoidismo subclínico (2) , pois, uma produção inadequada de TSH tem sido associada com maiores valores de pressão arterial sistólica e diastólica (6) , disfunção endotelial (7)(8) , estresse oxidativo (9) e desbalanço simpatovagal. (10)(11)(12) O exercício físico tem sido indicado como tratamento não farmacológico para doenças crônico-degenerativas como a hipertensão arterial, o diabetes e a obesidade. (13)(14)(15) Além de ser capaz de reduzir pressão arterial, a glicemia em jejum e a gordura corporal, vários estudos demonstram que o exercício físico melhora a função endotelial, a resistência vascular periférica e o balanço simpatovagal de hipertensos, diabéticos e obesos.…”
Section: Introductionunclassified